Exel Petroleum : fuel for Black Economic Empowerment - Hoven, Chris van der; Gaylard, Alison (London : Wits Business School, 2017)
In July 1997, Maurice Radebe moved from a successful, eight-year career at Shell Oil South Africa to take up the position of retail manager at Exel Petroleum, a Black Economic Empowerment (BEE) company newly started by energy and chemical company Sasol Oil and a consortium of black shareholders. His career prospects at Shell had been good. But South Africa was at an interesting juncture in its history, spirits were high because of the successful 1994 elections, and BEE was in its infancy. Radebe was intrigued about the opportunities in this new space and felt impelled to explore them further. Sitting in his sparsely furnished office in Rivonia (north of Johannesburg), Radebe wondered how to ensure the success of a new venture that would have to compete against the major global oil brands.
Originally published in Van der Hoven, C., & Gaylard, A. (2016). Exel Petroleum: Fuel for Black economic empowerment. WBS-2017-1. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Radebe, Maurice -- Case studies; Black Economic Empowerment (Program : South Africa) -- Case studies; Petroleum industry and trade -- South Africa -- Case studies